Optimasi Waktu Dan Biaya Dengan Kombinasi Metode Kerja Menggunakan Alat Berat Pada Pekerjaan Timbunan Main Dam Proyek Pembangunan Bendungan Tapin, Kalsel - Fuji Hafidz Pramudia; Ruzardi; Faisol AM (JOURNAL SAINS STUDENT RESEARCH, 2023)
Delays in completing a construction project often occur. One of the factors that can cause delays in development is that there are problems with land acquisition which cause the implementer/contractor to be unable to start carrying out work. Delays in project completion generally always result in losses, such as increasing costs, hampering operating profits resulting from the project, reducing the possibility of the implementer being able to start a new project, and can have an impact on the image of the implementer. The aim of this research is to speed up the duration of the implementation of the Main Dam Embankment Work for the Tapin Dam Construction Project, South Kalimantan. The research method used is an analysis of the existing work network and the relationship between time and cost in the process of accelerating work implementation using the time cost trade off method, namely by alternatively changing the combination of heavy equipment methods used using the help of the Microsoft Project program to determine the critical path. Based on acceleration by adding tools, the most effective is adding tools using ADT, because it produces the fastest completion time with a duration of 360 days but with an additional cost that is greater than the normal cost, namely IDR. 801.952.935. Compared to the normal cost of Rp. 767,651,068,342 and with a normal duration of 1000 days, the result is an additional cost of Rp. 34,301,867,554 with a reduced duration of 620 days.